Determinan Perilaku Disfungsional Auditor: Emotional Spiritual Quotient Sebagai Moderasi - Hadi, Azzahra Kania; Tarmizi, Muhammad Irfan (Politeknik Negeri Ambon, 2025)
Auditors hold a critical role in ensuring the reliability and accuracy of financial statements, which significantly influence stakeholders' decision-making processes. Auditors are responsible for providing assurance that financial statements are free from material misstatements by adhering to applicable professional standards. However, the occurrence of dysfunctional auditor behavior, often shaped by internal and external factors, poses a threat to audit quality and diminishes trust in audited financial statements. This study seeks to examine how internal factors (locus of control) and external factors (task complexity and work stress) contribute to dysfunctional auditor behavior. Employing a quantitative research approach, primary data were collected through surveys administered to 95 auditors working in public accounting firms in South Jakarta. Statistical analysis was conducted to test the proposed hypotheses, with Attribution Theory serving as the framework for analyzing the relationships between the variables. The findings reveal that task complexity, locus of control, and work stress are significant determinants of dysfunctional auditor behavior, and that Emotional Spiritual Quotient (ESQ) serves as a moderating variable in these relationships. This research contributes to a deeper understanding of the factors driving deviations in audit practices and offers recommendations to enhance audit quality, mitigate stress, and promote ethical behavior within public accounting firms.